EFEKTIVITAS PEMBELAJARAN BLENDED LEARNING DI MASA PANDEMI COVID-19 PADA MI QUBA KOTA SORONG - Agnesa, Oki Sandra; Astuti, Ninuk Vidya (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2021)
This study aims to determine: The effectiveness of blended learning at Madrasah Ibtidaiyah and the factors that influence it during the covid-19 pandemic. The study used qualitative methods with interview and documentation data collection techniques. The subjects in the study were teachers and students of MI Quba Sorong City. Data analysis used an interactive model from Milles and Huberman. The results of the study show that: the effectiveness of blended learning at Madrasah Ibtidaiyah is quite effective during the current pandemic. This can be seen from the completeness of the student's KKM which has increased from before. Students' enjoyment of blended learning is varied. then the teacher gives rewards to student learning outcomes so that students are more motivated in teaching and learning activities and stimulate other students to be more enthusiastic about improving learning outcomes. Time is flexible because the level of completion of students is different. As for the supporting factors to train students to be more independent, students can also search for information on the internet. While the inhibiting factors, teachers must-have skills, teachers need time to prepare learning, constrained internet network facilities and not all students have mobile phones.